KONSEP KESEJAHTERAAN DALAM EKONOMI ISLAM: PERSPEKTIF MAQASHID AL-SYARIAH - Fadlan, Fadlan (AMAL: Jurnal Ekonomi Syariah, 2019)
The writing of this paper aims to determine the extent of prosperity in the context of Islamic economics if it is relevant from the perspective of maqashid al-shariah. This welfare in economics has always been an endless discussion. Always the main topic, because welfare is always oriented to the material and self-interest. This orientation is certainly contrary to welfare when viewed from the perspective of Islamic economics, because it is not in accordance with the objectives of sharia (maqashid al-shari'ah) in general. In Islam, welfare is usually termed a problem, because it is a concept that encompasses all aspects of human life, whether it is individually or individually. Welfare from the view of maqashid sharia lies in five protections, namely protection of faith (al-din), soul (al-nafs), reason (al-'aql), descent (al-nasl), and wealth (al-mal). Welfare can not be separated from the ethical code of individuals in managing life. Because in economics a person's behavior will contribute to the benefit of himself, his family, and the environment. For this reason, the concept of mashlahah is also practiced in individual and community behavior. This results in consumers always having the nature of choosing goods and services that can providevalues mashlahah opaque. Keywords: Welfare, Islamic Economy, Maqashid al-Sharia